Elevated lead levels and adverse effects on natural killer cells in children from an electronic waste recycling area. (June 2016) - Zhang, Yu; Huo, Xia; Cao, Junjun; Yang, Tian; Xu, Long; Xu, Xijin
Abstract: Lead (Pb) has been proved to exert immunotoxicity to influence immune homeostasis in humans. To monitor the internal Pb level and evaluate its effect on natural killer (NK) cells and cytokine/chemokine concentrations, we recruited 285 preschool children from Guiyu, one of the largest electronic waste (e-waste) destinations and recycling areas in the world, and known to have high concentrations of Pb in the air, soil, water, sediment and plants. A total of 126 preschool children were selected from Haojiang as a reference group. Results showed that children in Guiyu, the exposed area, had higher blood Pb levels and lower percentages of NK cells than children from the reference area. A significantly negative association was found between the percentage of NK cells and increasing Pb levels. Moreover, children in Guiyu area had higher platelet counts and IL-1β concentrations, and lower levels of IL-2, IL-27, MIP-1α and MIP-1β were observed in the exposed children. These changes might not be conducive to the development and differentiation of NK cells. Taken together, the elevated Pb levels result in the lower percentages of NK cells, but also alter the levels of platelets, IL-1β and IL-27, which might be unconducive to the activity and function of NK cells. Highlights: A high blood Pb levels in preschool children in e-waste polluted area are observed. Elevated Pb levels are associated with the percentage change of NK cells. Dysregulated expressions in cytokines/chemokines are found in the exposed children. NK cell activities may be interfered by the alterations of cytokines/chemokines. Abstract : Elevated Pb levels result in the lower percentages of NK cells, but also alter the levels of platelets, IL-1β and IL-27, which might be unconducive to the activity and function of NK cells.